Being Janana Language and Sexuality in Contemporary India. - Nagar, Ila. (Milton : Routledge, 2019)
Being Janana focuses on same-sex desiring male-bodied subjects in Lucknow, India, and explores how they make meaning in the marginalization of their desire through language performativity. Along with their desire for other men, jananas maintain ostensibly heteronormatively and culturally defined masculine positions. This book argues for an intersectional approach to understanding janana life worlds and situates janana subjectivity in dialogue with social, cultural, linguistic, and legal happenings. In engaging with the full complexity of janana identities and experience, Ila Nagar calls for a reassessment of gender categories and a new understanding of power and sexuality amidst emerging Indian modernities. Derived from ethnographic research conducted over a period of twelve years, this book also reflects on the interaction between social actors and researchers, and critically examines the use of ethnography as a method in sociolinguistics and linguistic anthropology. It will be of interest to scholars from Anthropology, Asian Studies, Gender & Sexuality Studies, and Linguistics.
Cover; Half Title; Series Page; Title Page; Copyright Page; Dedication; Contents; Acknowledgments; Note on translation, pronouns, and names; 1 Introduction: entering the world of jananas; 2 Janana stories: living as a janana; 3 Jananas and hijras: perpetual conflict and attraction; 4 The janana community of practice: how the janana world works; 5 Negotiating identity through varying gender marking; 6 To feel like a woman: violence and the formation of the janana subject; 7 Janana subalterns; Epilogue; Appendix 1: rules of gender agreement in Hindi; Glossary; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Anthropology / General; Homosexuality -- India -- Lucknow; Sexual minorities -- India -- Lucknow; Masculinity -- India -- Lucknow; Gay men -- Language